eRegistries: Electronic registries for maternal and child health - Frøen, JF; Myhre, SL; Frost, MJ; Chou, D; Mehl, G; Say, L; Cheng, S; Fjeldheim, I; Friberg, I; French, S; Jani, J; Kaye, J; et al. (BioMed Central, 2016)
Background The Global Roadmap for Health Measurement and Accountability sees integrated systems for health information as key to obtaining seamless, sustainable, and secure information exchanges at all levels of health systems. The Global Strategy for Women’s, Children’s and Adolescent’s Health aims to achieve a continuum of quality of care with effective coverage of interventions. The WHO and World Bank recommend that countries focus on intervention coverage to monitor programs and progress for universal health coverage. Electronic health registries - eRegistries - represent integrated systems that secure a triple return on investments: First, effective single data collection for health workers to seamlessly follow individuals along the continuum of care and across disconnected cadres of care providers. Second, real-time public health surveillance and monitoring of intervention coverage, and third, feedback of information to individuals, care providers and the public for transparent accountability. This series on eRegistries presents frameworks and tools to facilitate the development and secure operation of eRegistries for maternal and child health.